2011
DOI: 10.1524/auto.2011.0906
|View full text |Cite
|
Sign up to set email alerts
|

Dezentrales autonomes Energiemanagement

Abstract: Zusammenfassung Bislang wird das Lastverschiebepotenzial an einzelnen Anschlüssen in den Verteilnetzen lediglich für einen Abgleich von Erzeugung und Verbrauch in Situationen besonders hohen oder besonders niedrigen Angebots erneuerbarer Energien in Betracht gezogen (z. B. Demand Side Management). Eine koordinierte Regelung über die Anschlüsse bezogener bzw. eingespeister Leistungen lässt sich aber auch für eine effizientere Auslastung bestehender Netze und zum Einhalten von Betriebsgrenzen hera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…There have already been a lot of research projects focusing on decentralized grid management (Conrad 2010;Lehnhoff 2010;Lehnhoff et al 2011). Most of the approaches used price incentives for an automated demand or supply response.…”
Section: Decentralized and Self-organized Grid Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…There have already been a lot of research projects focusing on decentralized grid management (Conrad 2010;Lehnhoff 2010;Lehnhoff et al 2011). Most of the approaches used price incentives for an automated demand or supply response.…”
Section: Decentralized and Self-organized Grid Managementmentioning
confidence: 99%
“…Hierarchical aggregation of sub grids with decentralized power system components through balancing group managers have been researched in detail (Lehnhoff 2010;Lehnhoff et al 2011). They concluded that it is possible to satisfy all actors and to provide necessary balancing power by means of decentralized assets in a possibly cheaper way compared to the current centralized control.…”
Section: Decentralized and Self-organized Grid Managementmentioning
confidence: 99%
“…Unlike the software presented in [4,14,15], any coordination mechanism that complies with the defined interface is compatible with Okeanos.…”
Section: Okeanosmentioning
confidence: 99%